Pengaruh Fasilitas, Aksesibilitas, dan Daya Tarik Terhadap Keputusan Berkunjung ke Objek Wisata Telaga Ngebel Ponorogo: Studi pada Masyarakat Kabupaten Ponorogo - Cahyanti, Hana Regita; Walyoto, Sri (Fakultas Ekonomi dan Bisnis Islam UIN Raden Mas Said Surakarta, 2024)
This research was conducted to determine the significant influence of the variables of facilities, accessibility and attractiveness on the decision to visit. Therefore, this research uses a quantitative approach. Using a purposive sampling technique with a sample of 157 respondents in Ponorogo Regency who had visited the Ngebel Lake tourist attraction twice. The types of data used are primary data and secondary data. The distribution of the questionnaire was carried out online via social media platforms such as WhatsApp which received 114 respondents and offline it was distributed by printing the questionnaire that had been made and then distributing it to 43 respondents. This research used multiple linear analysis, assisted by the IBM SPSS Statistics data analysis tool 23 to process data that has been taken by researchers. The results of this research suggest that the variables of facilities, accessibility and attractiveness have a significant and simultaneous influence on the decision to visit. So all the variables that have been studied show that they have an influence and are significant on the decision to visit the Telaga Ngebel Ponorogo tourist attraction.